Pengaruh Profitabilitas, Struktur Modal, Ukuran Perusahaan, dan Good Corporate Governance terhadap Nilai Perusahaan - Wulandari, Ayu Vivi; Kusumawati, Eny (Prosiding University Research Colloquium, 2022)
Firm value is an investor’s perception of the level of success of managers in terms of managing company resources. Firm value is often associated with an increase in stock prices. The higher the stock price of a company, the higher the value of the company. This study aims to determine the effect of profitability, capital structure, firm size, and good corporate governance on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The indicator used to measure firm value is Tobin’s Q. The sampling technique used in this study is Tobin’s Q. This study uses purposive sampling. The sample of this study consisted of 17 companies that met the sampling criteria. The analytical method used is multiple regression analysis. The results of hypothesis testing indicate that profitability, capital structure, independent board of commissioners, and managerial ownership have an effect on firm value. While the size of the company had no effect on the value of the company.